El Derecho internacional del medio ambiente y su relación con otras ramas del Derecho internacional (2015)
Protecting the environment has become one of the main topics of discussion around the world at various international conferences and organizations. The analysis of the issues regarding the environment such as pollution, protection of flora and fauna, and the detriment of the ozone layer, among other subjects, concerns the entire international community. International Environmental Law seeks to regulate relations between States, as well as between them and international environmental organizations. The study of the relationship with other branches of International Law such as International Human Rights Law, international Humanitarian Law and International Economic Law demonstrate the current interest of the international community on environmental topics.